Interaksi Sosial Orangtua Pekerja Industri Dalam Fenomena Daycare Di Tambun Selatan - Devy Putri Kussanti; Marlinda Irwanti Poernomo; Hayu Lusianawati (Cakrawala - Jurnal Humaniora, 2021)
Apart from being a place to leave children when both parents work, daycare is also seen as a place for child protection and fulfillment that is suitable for parents of industrial workers, especially the existence of daycare not far from the work location so as to minimize the time to pick up and drop children from work to and from work. The social interaction that occurs between the parents of industrial workers and the community in South Tambun regarding the daycare phenomenon lies in the daily life of industrial workers who have erratic working hours and have to leave their children in daycare which is seen as a daycare for city people who can afford it. This study uses a descriptive qualitative strategy or method with an in-depth interpretation of field findings based on existing facts. This research tradition is a phenomenological tradition that focuses attention on the conscious experience of an individual and uses an interpretive paradigm that seeks to find explanations about social or cultural events based on the perspectives and experiences of the person or organization under study. Using a symbolic interactionism analysis knife, the research describes three concepts, namely Mind, Self and Society from parents of industrial estate workers who leave their children in daycare.